Benefits of switching from latanoprost to preservative-free tafluprost eye drops: a meta-analysis of two Phase IIIb clinical trials - Uusitalo H (Dove Medical Press, 2016)
Hannu Uusitalo,1 Evgeniy Egorov,2 Kai Kaarniranta,3 Yuri Astakhov,4 Auli Ropo5 On behalf of the Switch Study Tafluprost Study Groups 1Department of Ophthalmology, SILK, University of Tampere, Tampere University Hospital, Tampere, Finland; 2Department of Ophthalmology, The Russian National Research Medical University, Moscow, Russia; 3Department of Ophthalmology, University of Eastern Finland, Kuopio University Hospital, Kuopio, Finland, 4Department of Ophthalmology, First Pavlov State Medical University of St Petersburg, Saint Petersburg, Russia, 5Global Medical Affairs, Santen Oy, Tampere, Finland Introduction: Glaucoma patients frequently exhibit ocular surface side effects during treatment with prostaglandin eye drops. The present work investigated whether glaucoma patients suffering from signs and symptoms of ocular surface disease while using preserved latanoprost eye drops benefited from switching to preservative-free tafluprost eye drops. Patients and methods: The analysis was based on 339 glaucoma patients enrolled in two Phase IIIb trials. The patients were required to have two symptoms, or one sign and one symptom of ocular surface disease at baseline, and at least 6 months preceding treatment with latanoprost eye drops preserved with benzalkonium chloride. All eligible patients were switched from latanoprost to preservative-free tafluprost for a total of 12 weeks. Ocular symptoms and ocular signs were evaluated at baseline and at 2 weeks, 6 weeks, and 12 weeks after commencing treatment with tafluprost. Intraocular pressure (IOP), drop discomfort, and treatment preference were evaluated to investigate the clinical efficacy and patient-related outcomes. Results: After 12 weeks of treatment with preservative-free tafluprost, the incidences of irritation/burning/stinging, foreign body sensation, tearing, itching, and dry eye sensation had diminished to one-third of those reported for preserved latanoprost at baseline. The incidences of blepharitis and corneal/conjunctival fluorescein staining had in turn decreased to one-half of those reported for preserved latanoprost. Severity of conjunctival hyperemia was halved during treatment with preservative-free tafluprost, and there was significant improvement in tear break-up time and tear production. A further reduction in IOP (~1 mmHg) was seen with preservative-free tafluprost compared with preserved latanoprost. Drop discomfort was alleviated during preservative-free tafluprost treatment, and an outstanding majority of patients (72%) preferred preservative-free tafluprost over preserved latanoprost. Conclusion: This meta-analysis confirmed that IOP remained at the same level after replacing benzalkonium chloride-preserved latanoprost eye drops with preservative-free tafluprost eye drops. Preservative-free tafluprost significantly decreased the symptoms and signs of ocular surface disease and outrated latanoprost in drop comfort and treatment preference. Keywords: Taflotan®, preserved latanoprost, Xalatan®, ocular surface disease, ocular symptoms and signs, IOP, patient-related outcome